Current status of scale insects (Hemiptera: Coccoidea) in the Italian vineyards (Bollettino di zoologia agraria e bachicoltura, 2024)
Nine species of Coccoidea occur in the Italian vineyards. Among the Pseudococcidae, the most important and widespread species is Planococcus ficus. Heliococcus bohemicus seems to be localized and is usually not considered as a pest. Among the Coccidae, Neopulvinaria innumerabilis was recorded as pest in north-eastern regions in the 1990s. Pulvinaria vitis, Parthenolecanium corni and Parthenolecanium persicae are less frequent. Infestations of the diaspidid Targionia vitis are sometimes recorded. Among natural enemies of grap mealybugs, Anagyrus pseudococci (Hymenoptera, Encyrtidae) is common on P. ficus. Predators belonging to Neuroptera Chrysopidae and Hemerobiidae, Coleoptera Coccinellidae and Diptera Chamaemyiidae are also frequently recorded on the same species. Concerning natural enemies of Coccidae, the parasitoid Coccophagus lycimnia (Hymenoptera, Aphelinidae) is often recorded on P. comi and N. innumerabilis as well as various species belonging to Chrysopidae, Coccinellidae and Chamaemyiidae. Coccophagoides similis (Hymenoptera, Aphelinidae) has been found associated with T. vitis. A number of predators are also reported as feeding on this species. Native natural enemies have a low impact on P. ficus populations in commercial vineyards, probably because their activity is affected by the use of pesticides. The role of natural enemies in controlling other Coccoidea seems to be more important. The impact of chemical control measures against Coccoidea is discussed within IPM strategies.
Keywords: grape; Coccoidea; economic importance; natural enemies